Analysis of capillary pressure effect on the seismic response of a CO2-storage site applying multiphase flow and wave propagation simulators. (August 2015) - Macias, Lucas A.; Savioli, Gabriela B.; Santos, Juan E.; Carcione, José M.; Gei, Davide
Abstract : Highlights: We introduce a new approach to simulate CO2 storage in a saline aquifer. We simulate seismic monitoring from the CO2 saturation distribution obtained. We perform a sensitivity analysis to evaluate capillary pressure effect. We reproduce the pushdown effect on seismic images that is observed in actual data. We detect that upward migration is delayed for higher values of capillary pressure. Abstract: We analyze the influence of capillary pressure on the seismic response of a saline aquifer, where CO2 has been stored in the Utsira Sand at the Sleipner field. For this purpose, we present a novel methodology integrating numerical simulation of CO2 –brine flow and seismic wave propagation, using a geological model that includes mudstone layers and natural apertures. The simultaneous flow of CO2 and brine in an aquifer is modeled by the differential equations that describe the two-phase fluid flow in porous media. The multiphase flow functions are determined from well-log data, using the relation between resistivity index, relative permeabilities and capillary pressure. Seismic monitoring is performed with a wave equation that includes attenuation and dispersion effects due to mesoscopic scale heterogeneities in the petrophysical and fluid properties. The fluid simulator properly models the CO2 injection and upward migration, obtaining accumulations below the mudstone layers as injection proceeds. Moreover, we are able to identify the time-lapse distribution of CO2 from the synthetic seismograms, which show the typical pushdown effect due to the spatial distribution of CO2 . Finally, a sensitivity analysis is performed by modifying the capillary pressure threshold in order to evaluate its effect over the CO2 plume and the corresponding synthetic seismogram.